PENGARUH PERSEPSI HARGA, CITRA PERUSAHAAN DAN CITRA MEREK TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN PADA APOTEK “DELA” DI SEMARANG (Proceeding Fakultas Ekonomi, 2014)
This study examines the effect of price perception, corporate image and brand image on customersatisfaction and loyalty. Data collected through the survey by distributing questionnaires to 120respondents. Data processing using SPSS Version 16th. The Results of the study showed that: (1)Perception does not affect the price of customer satisfaction. (2) The image of the company positive effecton customer satisfaction. (3) Brand image has positive effect on customer satisfaction. (4) Customersatisfaction has no effect on customer loyalty. (5) The price does not affect the perception of customerloyalty. (6) The image of the company positive effect on customer loyalty. (7) Brand image has positiveeffect on customer loyalty.Keywords: price perception, corporate image, brand image, customer satisfaction, customer loyalty